Data-Centric Business and Applications Evolvements in Business Information Processing and Management-Volume 1 - Kryvinska, Natalia; Greguš, Michal; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book discusses processes and procedures in information/data processing and management. The global market is becoming more and more complex with an increased availability of data and information, and as a result doing business with information is becoming more popular, with a significant impact on modern society immensely. This means that there is a growing need for a common understanding of how to create, access, use and manage business information. As such this book explores different aspects of data and information processing, including information generation, representation, structuring, organization, storage, retrieval, navigation, human factors in information systems, and the use of information. It also analyzes the challenges and opportunities of doing business with information, and presents various perspectives on business information managing.
Digital Communications and a Smart World -- WLAN Planning and Performance Evaluation for Commercial Applications -- Optimization of Traffic Fluctuations of a Telecommunication Service Delivery Platform Segment based on Forecasting using Ateb-functions -- Product Usage Data Collection and Challenges of Data Anonymization -- Challenges in Management of Software Testing -- The Role of Variety Engineering in the Co-creation of Value -- Enterprises Servitization for an Efficient Industrial Management a Survey-based Analysis -- Analysis of GDP and Inflation Drivers in the European Union -- Office 365 as a Tool for Effective Internal Communication in Corporate Environment.
Keywords: Computational intelligence; Artificial intelligence; Business information services; Econometrics; Computational Intelligence; Artificial Intelligence; Business Information Systems; Quantitative Economics